Modelo estratégico para fortalecer la asociatividad en los emprendimientos de turismo comunitario de la provincia de Manabí - Fernández Loor, María Valeria (2019)
The main objective of this research was to design a strategic model to strengthen the associativity in community tourism ventures in the province of Manabí, which will achieve interaction between the communities and the different public and private actors of the tourism sector. At the same time, they contribute to the reduction of existing problems, and they are identified in the community tourism management antecedents at the provincial and national levels, through the analysis of successful cases of community tourism centers, which are currently an alternative for development. For this reason, a methodology was proposed that allowed to obtain real data of the areas under study, and which served as a reference for the research sustenance and development of the proposal, which is linked to the specific objectives, and supported by the exploratory research - descriptive Thus, data collection was carried out in the socioeconomic environment of the communities, in order to analyze incidents and evaluate approaches that would allow structuring the strategic model, with their respective actions and strategies centered on four essential axes, such as: strengthening organizational, cultural revitalization, territorial management and solidary economy. In addition, each aspect of social and financial relevance was included, without excluding variables that could benefit and strengthen the associativity of the consolidated community tourism centers, and those that need the improvement of tourism services and infrastructure. Likewise, the management and participation of community actors was identified in the planning and implementation of community enterprises or family businesses, thus knowing the direct and indirect beneficiaries in the development of community tourism, which can serve as an example for several communities in the province of Manabí. All the mentioned, will be paid in the cultural revitalization that will have the populations that decide to be linked to the community tourism.